Hand hygiene at the root level: As a part of Competency-Based Medical Education - Danasegaran M, Shaik Khaja Moinuddin, Vijay Kumar Nair, Balaji P V, Vaseem D; Bhanuprakash Kolasani (International Journal of Advanced Science and Technology, 2020)
Competency-based medical education (CBME) has been introduced through the Graduate Medical Education Regulations (GMER) from the Medical Council of India. As per the new curriculum designed for medical graduates, one of the skill modules included is on hand hygiene which is the key feature to avert hospital infections. The current study targeted at determining the impact of skill module on hand hygiene awareness among first-year medical graduates. This was an interventional study carried out at Vinayaka missions medical college and hospital. A total of 82 first-year medical graduates were included in the study. Student awareness was tested using a self-structured, pretest questionnaire on hand hygiene. The student awareness was assessed using